How Do We Meet the Supportive Care and Information Needs of Those Living With and Beyond Bladder Cancer? - MacLennan, Sara Jane; MacLennan, Steven (Frontiers in Oncology, 2020)
This perspective paper presents the case for adopting a new approach to the design and delivery of supportive care for those with bladder cancer. It is our assertion that the design and delivery of supportive care for those diagnosed with bladder cancer needs to (1) build on existing research and available tools and (2) address current limitations due to lack of use of said tools, lack of understanding of research and needs, lack of a shared language, and method of assessment and evaluation. This, we argue, can be achieved through a network-based approach (1) focussed on the structure, process, and outcome of supportive care.